The effects of dietary threonine and porcine somatotropin dosage on nitrogen balance in finishing swine - J A Swanson; B R Schricker; D F Li; J A Hansen; Robert D Goodband; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1990)
Fifteen crossbred barrows were utilized to determine the effects of porcine somatotropin (pST) administration in combination with increasing dietary threonine levels on nitrogen retention and growth performance. Barrows averaging 147.3 lb were allotted in a split-plot arrangement with pST dosage (0, 4, or 8 mg/d) as the whole plot, and dietary threonine level (.45, .55, .65, .75, and .85%) as the subplot. These threonine values ranged from 112 to 212% of the dietary threonine estimate for finishing pigs (NRC 1988). All pigs within each pST dosage treatment received each diet for an 8-d period in a Latin square design. Diets were fed for a 4-d adaptation period followed by a 4-d total collection of feces and urine. Pigs were also weighed and bled at the end of each 8-d period. Increasing threonine level increased average daily gain (ADG), reduced feed intake (ADFI), and improved feed efficiency (F/G). Porcine somatotropin had no effect on ADG; however, pigs injected with 4 or 8 mg/d had numerical increases in ADG as threonine level increased. Feed efficiency improved as pST dosage increased. Daily threonine intake increased as dietary threonine level increased. However efficiency of threonine utilization for gain became poorer for control pigs as threonine intake increased, but pST-treated pigs had little change in efficiency of threonine utilization up to the .75 and .85% threonine levels for 4 and 8 mg/d pST dosages, respectively. There was a threonine x pST interaction for plasma urea concentrations, with control pigs having little change in urea concentrations whereas pigs injected with 4 mg/d pST had a decrease then an increase in urea concentrations and pigs injected with 8 mg/d had continual decrease in urea concentrations. Nitrogen retention (g/d) and percent nitrogen retention increased as dietary threonine level increased. However, pigs injected with either 4 or 8 mg/d pST had greater increases in nitrogen retention than control pigs. Biological value also improved as dietary threonine level increased, but again showed a greater improvement for pST-treated pigs than control pigs. These results indicate improvements in growth performance and nitrogen retention for finishing pigs fed increasing threonine levels. However, the data also indicated that the magnitude of response to added threonine was greater for pST-treated pigs, suggesting a possible threonine requirement of approximately .65% or 18 g/d.; Swine Day, Manhattan, KS, November 15, 1990
Keywords: Swine day; 1990; Kansas Agricultural Experiment Station contribution; no. 91-189-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 610; Swine; Repartition; GF; Performance; AA; Nitrogen